Is conscious awareness needed for all working memory processes?. Issue 1 (14th July 2016) - Soto, David; Silvanto, Juha
Abstract: Stein and colleagues argue there is no yet conclusive evidence for nonconscious working memory (WM) and that is critical to probe WM while ensuring null sensitivity to memory cues. While this stringent approach reduces the likelihood of nonconscious signaling for WM, we discuss existing work meeting this null sensitivity criteria, and, related work on nonconscious cognition in keeping with WM/awareness dissociations on the basis of a functional operational definition of WM. Further, because it is likely that WM is a nonunitary functional construct and visual awareness a gradual phenomenon, we propose that delineating the neural mechanisms for distinct WM types across different levels of awareness may prove the most fruitful approach for understanding the interplay between WM and consciousness.